2020
DOI: 10.1111/jam.14683
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antimicrobial combinatory effect of Cinnamomum cassia essential oil with 8‐hydroxyquinoline against Staphylococcus aureus in liquid and vapour phase

Abstract: Aims The objective of the study was to evaluate the antimicrobial interactions between two volatile agents, Cinnamomum cassia essential oil (CCEO) and 8‐hydroxyquinoline (8‐HQ) against Staphylococcus aureus strains in liquid and vapour phases. Methods and Results In vitro antimicrobial effect of CCEO in combination with 8‐HQ was evaluated against 12 strains of S. aureus by broth volatilization chequerboard method. Results show additive effects against all S. aureus strains for both phases. In several cases, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Moreover, a number of non-antimicrobial therapeutic agents, including ibuprofen, have been found to play a role in multidrug-resistant infections such as methicillin-resistant Staphylococcus aureus (MRSA). Furthermore, there is an increasing interest in the efficacy of herbal products and essential oils as a health remedy for the control of drug resistance issues, which may be due to the synergistic influence of bioactive compounds [ 75 , 76 ]. For example, GeloMyrtol (G. PohlBoskamp, Hohenlockstedt, Germany) is a notable herbal medicine used to treat asthma and sinusitis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a number of non-antimicrobial therapeutic agents, including ibuprofen, have been found to play a role in multidrug-resistant infections such as methicillin-resistant Staphylococcus aureus (MRSA). Furthermore, there is an increasing interest in the efficacy of herbal products and essential oils as a health remedy for the control of drug resistance issues, which may be due to the synergistic influence of bioactive compounds [ 75 , 76 ]. For example, GeloMyrtol (G. PohlBoskamp, Hohenlockstedt, Germany) is a notable herbal medicine used to treat asthma and sinusitis.…”
Section: Resultsmentioning
confidence: 99%
“…For example, GeloMyrtol (G. PohlBoskamp, Hohenlockstedt, Germany) is a notable herbal medicine used to treat asthma and sinusitis. GeloMyrtol is extracted from a variety of essential oils provided by Citrus limon , Camellia sinensis , Eucalyptus globulus , and Myrtus communis [ 76 ]. Therefore, we believe that the medicinal properties of Cassia timoriensis might have the potential to be developed as herbal products with antimicrobial properties in the future.…”
Section: Resultsmentioning
confidence: 99%
“…Much safer than cypermethrin, C. verum and C. cassia EOs as well as cinnamaldehyde provided a high toxicity against mosquitoes but are non-toxic to humans, other mammals, or bene cial insects [19][20]60 . Furthermore, they are easily degraded in the environment, and they have already been used for ages by Asian people as an anti-microbial agent in their local medicine [45][46][47][48] .…”
Section: Discussionmentioning
confidence: 99%
“…albopictus. We had selected to investigate these three EOs among numerous plant EOs because they have been reported to possess pharmaceutical, antifungal, antibacterial and insecticidal properties as well as to be safe for human and the environment [45][46][47][48] . EO combinations that showed a highly synergistic effect can be developed into effective adulticidal agents for controlling and managing Aedes mosquitoes in urban and rural areas as well as for controlling dengue diseases and other vector-borne diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Essential oils of Cinnamomum plants are widely used as promising antibacterial agents. Reports have indicated that the essential oils of C. camphora [3] and C. cassia [4,5] reverse antibiotic resistance and biofilm formation. Studies have also indicated that the C. zeylanicum (synonym of C. verum) has also found to be effective against multidrug resistant strains of clinical Shigella isolates [6].…”
Section: Introductionmentioning
confidence: 99%